Sleep quality and adverse incidents in secure mental health settings - Hartescu, Iuliana (The journal of forensic psychiatry & psychology, 2022)
Sleep disturbance has been associated with adverse incidents among male forensic inpatients. This study examined relationships between sleep quality and the occurrence/severity of adverse incidents among male and female patients in a secure psychiatric hospital setting. Sleep disturbance was assessed in 756 (361 female) patients at baseline (assessment 1), with 476 (253 female) patients followed up ≥1 month later (assessment 2). The occurrence and severity of adverse incidents was extracted from health records. Risk associated with sleep disturbance was assessed in adjusted binary logistic regression models with the occurrence of at least one adverse incident during the 7-day baseline period, or during the subsequent 30-day follow-up period as dependent. Prospective associations with adverse incidents among new cases of sleep disturbance, and ‘good sleepers’, were analysed using X2. Sleep disturbance and female gender were independently associated with a significantly elevated risk of adverse incidents in the baseline models. At follow-up, new cases of sleep disturbance showed the highest level of participation in adverse incidents, while ‘good sleepers’ showed both the lowest participation in, and the lowest impact scores resulting from adverse incidents. The management of sleep quality could help reduce participation in adverse incidents among inpatients in secure psychiatric environments.